ANALISIS BRAND IDENTITY HOTEL BUMI SURABAYA CITY RESORT MELALUI INSTAGRAM @bumisurabaya - Devi, Maria Diana Karunyabuddhi; Wahyuni, Jauhar (The Commercium, 2024)
In the midst of the competitive hotel industry, brand identity is very important. Brand identity is the main part of branding that managers offer to potential consumers. Brand identity is the theme of the hotel's promotion. The problem then is that not every hotel has a linear historical process. Changes in ownership or management require the hotel to offer a new brand identity. Hotel Bumi Surabaya is a hotel that builds a new distinctiveness in the form of brand identity as a resort hotel in urban areas. This research aims to analyze the strategy and development of Brand Identity presented by the Bumi Surabaya City Resort Hotel through the official Instagram account @bumisurabaya. The type of research used in this research is qualitative. The research method used in this research is descriptive. The data analysis techniques used are data collection, data reduction, data presentation and drawing conclusions. The results of the research stated that the Brand Identity built by the Bumi Surabaya City Resort Hotel went through gradual formation in the rebranding process and the formation of its image concept, namely City Resort. This concept was developed by the hotel using the brand name, logo, design and color, sound, vision and mission, tactical goals and tagline which can be seen on Instagram @bumisurabaya, so it can be concluded that the identity of the Bumi Surabaya City Resort Hotel is the City image concept. Resorts.